Compliance with nursing interventions for central venous catheter maintenance in pediatric patients - Castillo Cordova, Jose Angel (Universidad de Sonora, 2023)
Introduction: The central venous catheter is necessary in pediatric care; however, it is an important cause of nosocomial bacteremia, with 25% mortality. The nursing professional is responsible for the maintenance of the central venous catheter, in order to prevent local and systemic complications such as endocarditis and bacteremia related to intravenous treatment. Objective: To describe the nursing interventions for the maintenance of the central venous catheter in pediatric patients of a specialized hospital. Methodology: Observational, descriptive, cross-sectional design, sample made up of 85 nursing professionals who provided direct care to hospitalized children and received training, non-probabilistic sampling; the instrument used was a central venous catheter maintenance checklist, and data were collected with the observation technique. The survey complies with the ethical aspects of the general health law on research. Results: Nursing interventions were performed with an overall compliance of 90.1%; it is emphasized that 70.6% washed their hands before handling the device. Cleaning and maintenance of the insertion site was carried out by 98.8%, ports and connections were disinfected, and 92.9% lumens were identified. Conclusion: Nursing professionals performed interventions for the maintenance of the central venous catheter with a good compliance. However, the interventions with lower compliance that require improvement are hand hygiene, times for changing equipment and solutions, disinfection of ports and connections, which are essential to reduce infections in the bloodstream. In addition to future surveys about the professional and institutional factors associated with compliance.